Reactualizing ‘Aqal and Qalb in Islamic Education: A Deep Learning and Love-Based Approach within the Merdeka Curriculum Framework - Rusdiana Rusdiana; Husnul Yaqin; Hamdan Hamdan; Hidayat Ma’ruf (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study explores the reactualization of ‘aqal (intellect) and qalb (heart) in Islamic education within the framework of the Merdeka Curriculum, emphasizing the integration of deep learning and a love-based pedagogical approach. Contemporary Islamic education often tends to prioritize cognitive achievement while underemphasizing affective and spiritual dimensions, resulting in an imbalance in the holistic development of learners. This research aims to conceptually analyze how the synergy between ‘aqal and qalb can be strengthened through innovative learning paradigms that align with the principles of the Merdeka Curriculum. Using a qualitative library research method, this study examines relevant literature on Islamic educational philosophy, deep learning theory, and love-based curriculum approaches. The findings indicate that deep learning fosters critical thinking, reflection, and meaningful understanding, while a love-based approach nurtures empathy, compassion, and spiritual awareness. The integration of these approaches provides a holistic framework that aligns intellectual rigor with emotional and spiritual development. Furthermore, the Merdeka Curriculum offers a flexible and student-centered platform that enables educators to implement this integrative model effectively. The study concludes that the harmonization of ‘aqal and qalb through deep learning and love-based education can enhance the quality of Islamic education by producing learners who are intellectually competent, emotionally balanced, and spiritually grounded. This approach also reinforces the role of education as a transformative process that not only transmits knowledge but also cultivates character and moral integrity